Prevalência de hipertensão arterial em adolescentes escolares em Ibitinga: importância do histórico familiar - Casado, Haliny Miqueleto [UNESP] (Universidade Estadual Paulista (Unesp), 2010)
Hypertension (H) affects approximately 1,2 billion of people in the world. Among the main risk factors are weight excess, sedentary lifestyle, socio economic condition and family history of H. The main aim of this study was to assess the prevalence of hypertension in teenager scholars in Ibitinga, finding the role of family history of H and to correlates these results with nutritional condition, anthropometric variables and socio economic condition. This research analyzed 150 participants (50 teenager students and their parents) in public and private schools. All the volunteers had their weight (kg) and height (m) measured to calculate the body mass index (BMI). The students were classifieds from table of percentile of obesity (Centers for Disease Control and Prevention, CDC). The blood pressure (BP) was evaluated according to V Arterial Hypertension Brazilian Guidelines (VAHBG, 2006). The high values considered of BP were: ≥140x90 mmHg for adults and percentile >95 for teenagers. The socio economic condition was categorized from IBGE. Among the students, 36% had high BP and 20% borderline. The percentage of high BP were bigger in the public (44%) than private schools (28%), showing a negative correlation between socio economic condition and systolic BP (SBP, r=0.2857) and diastolic BP (DBP, r=0,0165). The prevalence of elevated BP was higher in the girls of public schools (47% vs 40% boys) and in the boys at the private schools (33% v s23%). Weight excess was present in 42% of children (12% obesity and 30% overweight). Again, public schools had prevalence of obesity (52% vs 3% in the private) which was not correlated with socio economic condition. Percentage of overweight and obesity were bigger in the girls of both public (54% vs 50% boys) and private (38% vs 25%) schools. Among the students with H, 67% were overweight. Elevated BP was found in 54% of the fathers and 32% of the mothers. With respect to nutritional condition, 56% of the...

A hipertensão arterial (HA) acomete cerca de 1,2 bilhões de pessoas no mundo. Dentre os principais fatores de risco estão excesso de peso, obesidade, sedentarismo, nível socioeconômico (NSE) e histórico familiar de HA. O objetivo deste estudo foi verificar a prevalência de HA em adolescentes escolares do município de Ibitinga, identificando o papel do histórico familiar de HA e correlacionar os resultados obtidos com o perfil nutricional, variáveis antropométricas e nível socioeconômico. Participaram do estudo 150 sujeitos (50 adolescentes escolares e seus respectivos pais), da rede pública e privada. Todos os voluntários tiveram peso (kg) e altura (m) avaliados para cálculo de índice de massa corporal (IMC). Os alunos foram classificados a partir da tabela de percentil de obesidade (Centers for Disease Control and Prevention, CDC). A pressão arterial (PA) foi aferida de acordo com as V Diretrizes Brasileiras de Hipertensão Arterial (VDBHA, 2006). Foram considerados valores elevados de PA: ≥140x90 mmHg para adultos e percentil >95 para as crianças e adolescentes. O NSE foi categorizado conforme IBGE. Dentre os alunos, 36% apresentavam PA elevada e 20% limítrofe. A porcentagem de PA elevada foi maior na rede pública (44%) que na rede privada (28%), havendo correlação negativa entre nível NSE e PA Sistólica (PAS, r=0,2857) e PA Diastólica (PAD, r=0,0165). Houve prevalência de PA elevada nas meninas da rede pública (47% vs 40% nos meninos) e nos meninos da rede privada (33% vs 23%). Excesso de peso estava presente em 42% das crianças (12% obesidade e 30% sobrepeso). Novamente, rede pública apresentou prevalência de obesidade (52% vs 3% na privada) que não se correlacionou com NSE. Porcentagem de sobrepeso e obesidade foi maior nas meninas, tanto na rede pública (54% vs 50% nos meninos) como na privada (38% vs 25%). Vale ressaltar que 67% dos alunos hipertensos estavam acima do peso. PA alterada (elevada+limítrofe)..
Keywords: Hipertensão - Diagnóstico; Educação física - Pesquisa; Família - Saúde e higiene; Obesidade; Hypertension Diagnosis